If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 = -3z + 20 Reorder the terms: -1 = 20 + -3z Solving -1 = 20 + -3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3z' to each side of the equation. -1 + 3z = 20 + -3z + 3z Combine like terms: -3z + 3z = 0 -1 + 3z = 20 + 0 -1 + 3z = 20 Add '1' to each side of the equation. -1 + 1 + 3z = 20 + 1 Combine like terms: -1 + 1 = 0 0 + 3z = 20 + 1 3z = 20 + 1 Combine like terms: 20 + 1 = 21 3z = 21 Divide each side by '3'. z = 7 Simplifying z = 7
| [x-3]=4x+9 | | 3(y-8)-2y=12 | | -9=r+(-2) | | 5.2/4.4 | | -4(d+12)=16 | | [-5x]=35 | | -18=3X-3 | | -29=15+y | | 6x+6(-3)=-8 | | 10q-9q=4 | | -j=-103 | | 2(3x+4)+x= | | 2-c=3 | | [-5x]=10 | | 9(2y+5)-2y-8= | | 5x^3-32x^2-21x=0 | | 8.8=x+x | | x-(-16)=-3 | | (2-w)(4w-3)=0 | | 14c-9c+5=15 | | 2(-7-8n)+(8-3n)=79 | | 6.3x-5+x-2.1= | | 8n-12+14=12n-4+4n+2 | | 5x(2x-3)=15 | | 51x^333(-16+9x^2)=0 | | 10x^2+46x=-24 | | 3n-2=1/2 | | 13a-12a=16 | | 4(a+3)-3a=3 | | 12x^3-12x^2+3x= | | 4z+6.2+3.8z+2.1z-1= | | 12z=.8z |